Regulation and Supervision of Fintech : Considerations for EMDE Policymakers - World Bank (Washington, DC, 2022)
Fintech is transforming the global financial landscape. It is creating new opportunities to advance financial inclusion and development in Emerging Markets and Developing Economies (EMDEs), but also presents risks that require updated supervision policy frameworks. Fintech encompasses new financial digital products and services enabled by new technologies and policies. Although technology has long played a key role in finance, recent fintech developments are generating disruptive innovation in data collection, processing, and analytics. They are helping to introduce new relationship models and distribution channels that challenge traditional ways of finance, while creating additional risks. While most of these risks are not new, their effects and the way they materialize and spread across the system are not yet fully understood, posing new challenges to regulators and supervisors. For example, operational risk, especially cyber risk, is amplified as increasing numbers of customers access the financial network on a 24 by 7 basis. Likewise, increased reliance by financial firms on third parties for provision of digital services, such as cloud computing, may lead to new forms of systemic risks and concentration on new dominant unregulated players such as big tech firms. This note aims to provide EMDE regulators and supervisors with high-level guidance on how to approach the regulating and supervising of fintech, and more specific advice on a few topics. Preserving the stability, safety, and integrity of the financial system requires increased attention to competition and ensuring a level playing field and to emerging data privacy risks. As a general principle, policy response should be proportionate to risks posed by the fintech activity and its provider. While striking the right balance can be challenging in the absence of global standards, the IMF-World Bank Bali Fintech Agenda (BFA), along with guidance by Standard Setting Bodies, provides a good framework for reference.